3D-printed, ceramic porous metasurface wick: Hexagonal-prism unit-cell capillary evaporator - Franceschetti, Lorenzo; Kameya, Yuki; Kaviany, Massoud (International journal of heat and mass transfer, 2025)
A hexagonal-prism unit-cell based alumina evaporator wick with 150μm struts and 375μm wick thickness is designed and fabricated with 3D-printing using projection micro stereolithography and post debinding and sintering. The evaporator wick capillary pressure, permeability, effective thermal conductivity, and specific thermal conductance are calculated using static surface-energy minimization for the liquid meniscus-capillary pressure and 3-D CFD simulations. In comparison to a close-packed, sintered copper particle (average diameter of 78μm) monolayer wick used in a similar, previous experiment, the ceramic wick has a much larger capillary-viscous critical heat flux qCHF,c−v. However, the specific thermal conductance of the ceramic wick is about 1/10, due to its larger thickness and lower effective thermal conductivity, such that the wick superheat critical heat flux qCHF,sh controls the upper limit of its performance. The ceramic hexagonal-prism unit-cell wick outperforms this monolayer sintered-copper wick, when used for open-system evaporation. The experiment uses water and a 10 mm × 20 mm partially submerged alumina wick with contact heating area of 8 mm × 8 mm, under incremental increase in the heating rate up to the wick superheat limit. Infrared thermometry (with an estimate of the wet-wick surface emissivity) is used for the wick surface temperature. The 3-D numerical simulations show the fin effect in the lower, unheated wick section and the predictions, including the average wick-surface temperature, are in good agreement with the measurements. [Display omitted] •A 3D-printed ceramic evaporation wick metasurface is fabricated, tested, and simulated.•IR thermometery measurements of the wick surface temperature agree with predictions.•Ceramic, hexagonal-prism unit-cell wick is capable of high evaporation dryout limits.•The ceramic wick superheat limit is lower (and reached) than its capillary-viscous limit.•The wick’s thermal properties are optimized subject to fabrication dimension limitations.